Thermal and mechanical properties of PVDF/PANI blends - Malmonge, Luiz Francisco [UNESP] (2010)
Poly(vinylidene fluoride)/polyaniline blends of different composition were synthesized by chemical polymerization of aniline in a mixture of Poly(vinylidene fluoride) and N,N-dimethylformamide and their thermal and mechanical behavior was investigated as a function of the polyaniline doping level and the composition using thermogravimetric analysis, differential scanning calorimetry, dynamic mechanical analysis and tensile tests techniques. The results showed the blend obtained presents a good thermal stability with low weight loss up to 300 ºC, assigned to water and solvents evaporation. The glass transition and melting point is not affected by the PANI content in the blend, showing that polymers are no miscible. The films produced present a good sustainability; however the presence of the conducting polymer in the blend increases the tensile strength and the Young modulus, while diminishes the elongation at break, as compared to pure PVDF.